Sistem Pemesanan Makanan Berbasis Mobile dengan Metode First Come First Served (FCFS) di Restoran Dapur Hanhil Bekasi - Nadjib Kurnia Budiawan; Kusdarnowo Hantoro (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2024)
Research to develop a First Come First Served (FCFS) mobile application system for ordering food at Dapur Hanhil Restaurant in Bekasi. This technology makes it easy for clients to place food orders using mobile applications, prioritizes orders based on first-come, first-served scheduling, and simplifies ordering procedures. This approach is expected to improve the dining experience for customers by combining mobile technology with FCFS processes. It is hoped that the research findings can provide direction for creating such systems in the fast food restaurant sector. The aim of the research is to create an application system for mobile food ordering at Dapur Hanhil Restaurant in Bekasi. The approach uses the First Come First Served (FCFS) method. The results of the research are to develop a First Come First Served (FCFS) mobile application system for ordering food at Dapur Hanhil Restaurant in Bekasi.